The Tradition of Othuvar in Temples -A Cultural Musicology study based on the Saiva temple tradition in Sri Lanka - Suhanya, A. (Asian Research Association, 2022)
The early Siva community identify the Singing is the easiest way to pray to God and reaching his salvation. From the earliest times in the Saiva tradition, the Nayanmars and Alvars who descended from Karaikkalammaiyar, followed this way and dissolved with the power of God not only this, with the help of history of Saiva we can understand, these Nayanmars and Alvars were not only practice this style of praying in their own life,as well as they insist the community to follow this method of their religious life also. In the Saiva tradition, those who greet the Lord with music are known by the special name of 'Oduvars'. This Oduvar tradition, which originated from Karaikkalammaiyar in the history of Sivasim, has continued in Hindu temples in Sri Lankaup to now.As far as Sri Lanka is concerned, history has maintained a close relationship with Tamil Nadu for a long time in culture, religion, customs and many other social contexts. It would not be an exaggeration to say that even though Sri Lanka has been under foreign rule for a long time, it is the work of these readers to preserve Sivasim and Tamilism and pass it on to the next generation.This article describes the work done by the Oduvars in Jaffna, the place where Saivism flourished in Sri Lanka
Keywords: Oduvars; Devotion; Thirumurai; Tamil Isai; Rendering